Любовник смерти: роман / Б. Акунин - Акунин Борис (Новый детективъ, 2008)
Экземпляры: ф.22 (2007) / Инвентарный номер: 51423 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL